Utilisation of nutrients by cucumber plants oil rockwool substrate - Rácz, I-né; Szőriné Zielinska, A. (International Journal of Horticultural Science, 2005)
Cucumber production by soil less culture on rockwool substrate in Hungary is an open system regarding its water and nutrient supply. Environmental and economical reasons require the recycling of nutrients of the system. Experiments have been planned in order to estimate the utilisation of individual nutrient elements applied. All around the vegetation period, chemical analyses monitored the depletion of the elements initially administered by sampling the solutions at successive phases from the injection to the overflow. The results have been compared with earlier experiences refering to general rules. It has been stated that the intensity of photosynthesis is decisive in determining the composition of the overflow. The less changes are observed during the period of frequent watering.The absorption of the nutrient elements varied between 25-51% deperiding on the individual elements. The differences are significant. Further examinations are needed in order to clear:• which are the main elements of technology, which are decisive in utilisation of nutrients• what are the possibilities of the secondary utilisation of nutrients.